Contemporary Jurisprudence: A Study of Jurisprudence on Interfaith Marriage - Maslathif Dwi Purnomo; Lulu Malona Siregar; Mhd. Irsan Akbar (Jurnal Sahabat ISNU SU, 2025)
Interfaith marriage is an issue that has given rise to serious debate in contemporary Islamic jurisprudence. Although there is an explicit text in the Qur'an that permits Muslim men to marry women from the People of the Book (QS. al-Māidah [5]: 5), many contemporary scholars such as Yusuf al-Qaradawi and Quraish Shihab consider this permissibility to be contextual and not absolute. In the context of modern society that is increasingly plural and secular, interfaith marriage is seen as threatening household stability, children's education, and the preservation of Islamic faith within the family. Therefore, contemporary Islamic jurisprudence encourages a review of this permissibility through the maqāṣid al-syarī'ah approach, which emphasizes the protection of religion, offspring, and household harmony. In Indonesia, this issue is also affirmed in positive law as stipulated in Law Number 1 of 1974 concerning Marriage, which requires marriages to be conducted according to the laws of each religion. This paper aims to analyze the views of classical schools of thought and the thoughts of contemporary Islamic scholars on the practice of interfaith marriage and evaluate its relevance in the social and legal context of contemporary Indonesia. This research uses a normative qualitative approach with descriptive-analytical methods on fiqh texts and laws and regulations.